Rancang Bangun Sistem Informasi Pimpinan Daerah 114 Tapak Suci Putera Muhammadiyah Pekanbaru Menggunakan Model Waterfall - Pratama Yudha, Muhammad Ryan; Rahmad Al Rian; Melly Novalia (Computer Science and Information Technology, 2025)
In Tapak Suci, particularly in the Pekanbaru region, the organizational leadership structure in Indonesia comprises four levels: the school (perguruan), branch leadership (pimpinan cabang), regional leadership (pimpinan daerah), provincial leadership (pimpinan wilayah), and central leadership (pimpinan pusat). Currently, the management of member data, ranking data, and other related information is still conducted manually. This process is often time-consuming, inaccurate, and difficult to retrieve. Consequently, the organization's management faces challenges in obtaining fast and accurate information to support decision-making. Furthermore, manual data management is prone to human error and data loss.Information system technology offers a potential solution to these challenges. This research uses a Research and Development (R&D) methodology by using an integrated information system to enable more efficient, accurate, and structured data and information management. The development process adheres to the Waterfall paradigm, which comprises the phases of system design and requirement analysis., coding, testing, and system maintenance.The result of this research is a web-based information system for managing the activities of 114 Regional Leaderships (Pimpinan Daerah) of Putera Muhammadiyah. This data management system is designed for two types of users: PIMDA administrators and Branch administrators. The information system is expected to improve the efficiency of organizational management.